Factors affecting English performance between students residing in tourist and non-tourist areas - Tuti Hidayati; Sari Diana; Faizatul Husna; David D Perrodin (Studies in English Language and Education, 2023)
Living in a tourist area is frequently viewed as an advantage for students learning English as it provides more opportunities to practice the language. The present study looked at the English performance of students residing in tourist and non-tourist areas and explored how they learned English and the factors affecting their language performance. A comparative study was conducted using a concurrent mixed-method approach. The data were collected through documents, tests, and interviews and analyzed quantitatively and qualitatively to examine differences and determine the main themes between the respective groups. The result of the study indicates that the two groups differed statistically in terms of English school grades and speaking test scores with large effect sizes (d = 3.26 and d = 1.28), respectively. Even though the proficiency test did not show a significant difference (p = .72), the non-tourist group outperformed the tourist group in all assessment types. The interviews revealed that regardless of the different attributes and sites where students lived, the two groups were similar in how they learned English. The main factors affecting the English language performance of both groups were (1) strong motivation, (2) exposure to English through songs, games, movies, and  social media, and (3) family support.